The suitability of applying the competencies system in the Public Authority for Applied Education Proposed study (case study of civil engineering departments) - Naseeb, Ahmed Gohar (Journal of Educational and Psychological Sciences, 2023)
There are many systems and patterns for preparing and vocational training for technicians, while those interested are keen to develop methods for that. While the student in university education studies theoretical sciences alongside the practical side according to specialization and its nature, the pre-university education specialized in vocational study comes to provide a more practical side besides studying a simple theoretical part, which guarantees Graduating qualified and experienced workers because their study was work and not just information. However, some new patterns have emerged recently for the preparation of these cadres that differ according to the social and economic environment, the general field of work, and the country’s orientation, direction and resources. Some systems have fallen behind in keeping pace with the massive development in life and have become traditional systems that are not commensurate with the nature of events and modern technologies, and preparing a technician who is able to understand modernity and modern technology has become a difficult thing in the phase of those systems. This research paper talks about one of the modern applied systems that has spread recently as a way to prepare skilled technicians. It is presented as a proposal to modernize the civil engineering specialization in the Public Authority for Applied Education. It studies the possibility of applying the competencies system in developing this department. Many researches related to this system have been studied and the working system is studied in The Authority, taking into account the available capabilities, has formulated recommendations indicating the findings of the study and presented them as a proposal for development and placed them in the hands of decision makers.